PERAN GURU PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DALAM MEMBENTUK KARAKTER RELIGIUS SISWA MELALUI AJARAN TRI KAYA PARISUDHA DI SD N 7 BANJAR ANYAR KECAMATAN KEDIRI KABUPATEN TABANAN: Guru Agama Hindu, Pendidikan Agama Hindu, Pendidikan Karakter Religius - Meita, Meita Prabaswari (UHN IGB Sugriwa Denpasar, 2025)
The importance of religious character education that can be built at an early age at the elementary school level is in overcoming student deviant behavior, various efforts are made by educators to change student character.The problems that will be discussed in this interview are: (1) What is the role of Hindu religious education and character teachers in shaping students' religious character through the teachings of Tri Kaya Parisudha at SD N 7 Banjar Anyar (2) What are the obstacles to learning Tri Kaya Parisudha in forming students' religious character at SD N 7 Banjar Anyar (3) What efforts are made by Hindu religion and character teachers in forming students' religious character through the teachings of Tri Kaya Parisudha at SD N 7 Banjar Anyar. This research aims to find out the role of Hindu religious teachers in forming religious character education, the obstacles and efforts in forming religious character education, as well as the results of forming character education by Hindu religious teachers. The problems in this research are studied using role theory, constructivist theory. and character theory. This research uses data collection techniques of observation, interviews, literature study, documentation. The data that has been collected is analyzed using qualitative descriptive analysis methods. Based on the results of research and data analysis, it shows that (1) the role of Hindu religious teachers in developing character education in students is through curricular activities such as intracurricular and extracurricular. (2) Obstacles from learning Tri Kaya Parisudha in forming the religious character of students at SD Negeri 7 Banjar Anyar. (3) Efforts made by Hindu Religion and Character Education Teachers to form religious characters who are religious, honest, independent, hard working, tolerant, disciplined, responsible and care for the environment. Referring to the results of these observations, it can be seen that the role of teachers of Hindu religious education and character plays a very important role in the success of students' education and has gone very well based on problem analysis with the theory used in the research. Keywords: Hindu Religion Teacher, Hindu Religious Education, Religious Character Education